Pengaruh Kecepatan Angin terhadap Daya Keluaran Turbin Angin Tipe Hellical Savonius dengan 3 Sudu (Jurnal Inovasi Mesin, 2021)
This research aimed to find out the effect of wind speed on power output of savonius type wind turbine with 3 hellical blades. Variations of wind speed were obtained through a predetermined time and location of observation. The data collected consist of wind speed, voltage, electric current, RPM, and the power. The observation showed that wind speed affected the power turbine output. Time and location of the test that did not yield power output namely: at 09.00 am in the Marina Beach and at 12.00 pm in the GSG UNNES. The highest output power obtained at 06.00 pm in both areas. It was concluded that the wind speed in the morning and midday yield in lowest power output of turbine, while in the afternoon produce the highest power.